Respon Petani Terhadap Kegiatan Kelompok Tani Hutan Giri Jaya di Desa Nagrog Kecamatan Cicalengka Kabupaten Bandung - Hardiyanto, Tito; Sujaya, Dedi Herdiansah; Ramdan, Mochamad; Pardani, Cecep (Universitas Galuh, 2026)
Forest Farmer Groups are part of forest-edge communities who serve as the main actors in grassroots forestry development and key targets of forestry extension programs. Understanding farmers’ responses to KTH activities is essential for evaluating the success of such initiatives. This study aimed to analyze farmers’ responses and identify challenges in implementing Forest Farmer Groups activities at Giri Jaya, Nagrog Village, Cicalengka District, Bandung Regency, conducted from September to October 2025. The study applied a scoring system (1–3) to measure response levels—high, medium, and low. A census method was used to include all 20 KTH Giri Jaya members as respondents. Data were collected through interviews, field observations, and literature review. The findings revealed that KTH Giri Jaya successfully enhanced farmers’ knowledge and attitudes, as reflected in high average scores of 34.80 and 18.85, respectively. These results indicate that participatory extension effectively fostered motivation and social responsibility among members. However, technical skills remained moderate (13.20), highlighting the need for more practical training and mentoring. Overall, the total response score (66.85) demonstrated a strong positive impact of KTH activities on farmer capacity building. Nonetheless, continuous learning through training and “learning by doing” is required to strengthen technical competence. The main challenges faced were uneven input distribution and the dry season, which affected work performance and reduced seedling quality.